2022
DOI: 10.1007/s40200-022-01101-4
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective activity of anethole- rich fraction from aromatic herbs on junk food induced diabetic nephropathy in rats

Abstract: Purpose This study was carried out to study the effect of anethole rich fraction on the Diabetic Nephropathy (DN) rats, and explore the mechanisms. Methods Male wistar rats were grouped into 4 (n = 6 per group): Control, junk food fed DN induced rats, low dose and high dose groups. DN was induced by oral junk food feeding. They were monitored for blood glucose levels and urine protein content at regular intervals. At the end of the study, the biological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The positive effects of fennel products on diabetes are attributed to anethole, which is the quantitatively dominant component in fennel essential oil. Vellapandian et al have previously demonstrated that the administration of anethole-rich extracts can ameliorate renal damage in diabetic rats at a dose of 100 mg anethole/kg [ 23 , 24 ]. Similar results have been obtained by Samadi-Hoshahr et al, at a dose of 80 mg anethole/kg [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The positive effects of fennel products on diabetes are attributed to anethole, which is the quantitatively dominant component in fennel essential oil. Vellapandian et al have previously demonstrated that the administration of anethole-rich extracts can ameliorate renal damage in diabetic rats at a dose of 100 mg anethole/kg [ 23 , 24 ]. Similar results have been obtained by Samadi-Hoshahr et al, at a dose of 80 mg anethole/kg [ 25 ].…”
Section: Discussionmentioning
confidence: 99%